Docking-based development of purine-like inhibitors of cyclin-dependent kinase-2 - Otyepka, M; Krystof, V; Havlícek, L; Siglerová, V; Strnad, M; Koca, J (Journal of medicinal chemistry, 2000)
The cell division cycle is controlled by cyclin-dependent kinases (cdk), which consist of a catalytic subunit (cdk1-cdk8) and a regulatory subunit (cyclin A-H). Purine-like inhibitors of cyclin-dependent kinases have recently been found to be of potential use as anticancer drugs. Rigid and flexible docking techniques were used for analysis of binding mode and design of new inhibitors. X-ray structures of three (ATP, olomoucine, roscovitine) cdk2 complexes were available at the beginning of the study and were used to optimize the docking parameters. The new potential inhibitors were then docked into the cdk2 enzyme, and the enzyme/inhibitor interaction energies were calculated and tested against the assayed activities of cdk1 (37 compounds) and cdk2 (9 compounds). A significant rank correlation between the activity and the rigid docking interaction energy has been found. This implies that (i) the rigid docking can be used as a tool for qualitative prediction of activity and (ii) values obtained by the rigid docking technique into the cdk2 active site can also be used for the prediction of cdk1 activity. While the resulting geometries obtained by the rigid docking are in good agreement with the X-ray data, the flexible docking did not always produce the same inhibitor conformation as that found in the crystal.
Keywords: molekulární konformace; Ligands; Models, Molecular; Molecular Conformation; Catalytic Domain; ligandy; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; cyklin-dependentní kinasy; Cyclin-Dependent Kinases; protein-serin-threoninkinasy; cyklin-dependentní kinasa 2; Purines; molekulární modely; Drug Design; proteinkinasa CDC2; CDC2 Protein Kinase; Protein Serine-Threonine Kinases; katalytická doména; puriny; racionální návrh léčiv; inhibitory enzymů; Cyclin-Dependent Kinase 2; CDC2-CDC28 Kinases; kinasy CDC2-CDC28; Enzyme Inhibitors